Retail City: The Relationship between Place Attractiveness and Accessibility to Shops - Özge Öner (Research Institute of Industrial Economics (IFN), 2015)
This paper explores the role of retailers as an urban amenity. Using data for Swedish rural and city municipalities for 2002-2008, accessibility to shops' measures are constructed for the shops in the municipalities and in the hosting regions separately to examine the relationship between consumption possibilities and place attractiveness in a spatial continuum. Place attractiveness is proxied by a Q ratio for Swedish housing investment based on Tobin's Q. Access to stores within municipal market boundaries is found to be relevant for the place attractiveness of city municipalities, whereas no such relationship is evident for rural municipalities.
Keywords: L81; R12; R14; R31; 330; Housing; Urban amenities; Retail; Q theory; Regional hierarchy